Cisplatin and ozone adjuvant to surgical excision of corneal squamous cell carcinoma in a horse (Research, Society and Development, 2021)
Squamous cell carcinoma (SCC) is a neoplasm of squamous epithelium that usually affects the head, orbital and genital regions of horses. Solar irradiation is one of the main causes, especially in depigmented and hair-free areas. The article reports the case of a male horse, aged 15 years, who had a nodular infiltrative mass over the entire corneal surface, suggesting granulation tissue adhered to the cornea. On cytological examination, the mass was indicative of squamous cell carcinoma. Numerous medicinal characteristics of ozone are already well recognized and reported by the scientific community, among them: its antioxidant, bactericidal, fungicidal, immunostimulating action, aid in wound healing and antitumor activity. In view of this, surgical excision, corneal curettage, intralesional chemotherapy with the use of cisplatin and ozone therapy took place. The treatment demonstrated that the surgical excision, associated with the use of cisplatin and ozone therapy in the post-surgical period, showed efficient results, with a favorable prognosis, since after eighteen months of the animal's medical discharge, the owner did not report recurrence.